PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IV SD NEGERI 035 SEKELADI - ', Parinten; Alpusari, Mahmud; ', Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: background in this study is that the results of the research students studying PKn class action (PTK) and the application of the Cooperative Learning Model Type TSTS. This research aims to improve the learning results of PKn grade IV SD Negeri Sekeladi 035 Sub White Ground with a number of students shebaniah 20 students. This research was conducted with two cycles, each cycle consisting of 2 times with 1-time repeats daily. Data collection instruments in the research is the observation sheets, sheet teacher observation of student test results and learn.The results of the data analysis activities teacher on cycle I first encounter and second encounter 65.63% increase to 68.75%. Cycle II 78.13% first meeting and the second meeting increased to 86,00%. Furthermore the results of the data analysis of student activity on the cycle I first encounter and second encounter 67.50% increase to 72.50%. Cycle II first meeting 77.50% and second meeting rose to 84.00%. From the results of this research were obtained results has increased student learning that is the average student learning outcomes on the base score is increased 69.75 cycle I became 79.50 increased again in cycle II 80.75. For ketuntasan study on base score is 9 people (45%) increase in cycle I became 17 people (85%) and increased again in the cycle II to 19 people (95%) with categories completely.Thus it can be concluded that Cooperative Learning Model of applied Type TSTS can improve learning outcomes PKn grade IV SD Negeri Sekeladi 035 Sub White Land.Keywords: models of Cooperative Learning, results of TSTS type PKn.